Journal of Pediatric Endocrinology and Metabolism (De Gruyter, 1985)
The Journal of Pediatric Endocrinology and Metabolism (JPEM) is the only international journal dedicated exclusively to endocrinology in the neonatal, pediatric and adolescent age groups, and publishes the results of clinical investigations in pediatric endocrinology and basic research. JPEM publishes Review Articles, Original Research, Case Reports, Short Communications and Letters to the Editor.